Sprinkler Technology Improves Broiler Production Sustainability: From Stress Alleviation to Water Usage Conservation: A Mini Review - Liang, Yi; Tabler, George T.; Dridi, Sami (Frontiers in Veterinary Science, 2020)
Global poultry production is facing several challenges including a projected increase in global demand for high quality animal proteins and the need to adapt to environmental contrasts including heat stress and the increasing pressure on natural resource (water, land, and energy) availability. Heat stress is one of the most challenging stressor to poultry production because of its strong adverse effects on welfare, production, mortality, and water usage. Most commercial poultry houses worldwide are equipped with a combination of tunnel ventilation and evaporative cooling system (pads, fogging, or low-pressure misting systems) as the status quo to overcome heat stress. Despite prior investments in these systems, critical problems continue to impede poultry production efficiency, which still declines during hot seasons. In fact, these systems tend to saturate the barn air with moisture (>70% relative humidity) which is counterproductive to the bird's own physiological ability to cool itself by hyperventilation (evaporative heat loss). The second challenge with these systems is the significant amount of water usage. This review will summarize some of the benefits of surface wetting of birds through sprinkler technology (SPRINK) that has higher efficiency to maintain birds' comfort with significantly less use of cooling water. Despite higher air temperature and lower relative humidity in the sprinkler house, the SPRINK decreased broiler body core temperature, reduced systemic and intracellular stress, preserved intracellular energy, and averaged six points better FCR compared to evaporative cooling system.